(untitled) (Proceedings of the European Wave and Tidal Energy Conference, 2025)
Hybrid wind-wave systems combine a floating offshore wind turbine (FOWT) with wave energy converter (WEC) units, boosting overall power production and reducing operating expenses, thereby decreasing the Levelised Cost of Energy. Amongst the various WEC concepts to advance to the stage of full-scale prototype development, the Oscillating Water Column (OWC) stands out as one of the most promising. The primary objective of this study is to support the development of a floating, hybrid OWC – wind energy module, intended for deployment in the Fiji Islands. The research integrates the University of Maine’s VolturnUS-S Semi-Submersible FOWT with three cylindrical OWCs embedded within its platform. Experimental investigations evaluated the power performance of the OWCs and the dynamic response of the combined system under various regular wave conditions. Different OWC orifice plate configurations were also tested to assess the impact of power take-off (PTO) damping on platform stability and power generation efficiency. Results indicate that incorporating OWC WEC units significantly improves platform stability compared to the stand-alone VolturnUS-S platform. Additionally, a spatial variation in power generation was observed across the three OWCs, with the aft chamber producing more power than the port and starboard chambers. These findings highlight the substantial development potential of the combined OWC – wind concept, due to its increased power output and improved platform stability. The outcomes of this study are expected to inform the design, construction, and operation of practical hybrid wind – wave energy systems.